Co-activation of Taxonomic and Thematic Relations in Spoken Word Comprehension: Evidence From Eye Movements - Xu, Pingping; Qu, Qingqing; Shen, Wei; Li, Xingshan (Frontiers in Psychology, 2019)
Evidence from behavior, computational linguistics, and neuroscience studies supported that semantic knowledge is represented in (at least) two semantic systems (i.e., taxonomic and thematic systems). It remains unclear whether, when and to what extent taxonomic and thematic relations are co-activated. The present study investigated the relative strength of the co-activation of the two types of semantic representations when both types of semantic relations are simultaneously presented. In a visual-world task, participants listened to a spoken target word and looked at a visual display consisted of a taxonomic competitor, a thematic competitor and two distractors. The growth curve analysis revealed that although taxonomic competitors were fixated more than thematic competitors, and these two types of competitors started to receive more fixations than distractor in a similar time window, which suggested that taxonomic and thematic relations are co-activated by the spoken word.